PKBM'S CONTRIBUTION TO IMPROVING THE QUALITY OF NON-FORMAL EDUCATION IN CIANJUR - Muhammad Ramdhan (BAIK Publishers, 2025)
Non-formal education is a strategic solution to bridge the gap in education in areas with limited access, including Cianjur Regency. Community Learning Activity Centers (PKBM) as non-formal educational institutions have a central role in providing equal education services, literacy, life skills, and community empowerment. This study aims to analyze the contribution of PKBM to improving the quality of non-formal education in Cianjur, as well as identifying supporting and inhibiting factors in its implementation. The research method used is a qualitative approach with case studies on several PKBM in the Cianjur area. The results of the study indicate that PKBM plays a role in reducing school dropout rates, improving the skills of students, and expanding access to education. However, challenges such as limited funds, educators, and community participation are still major obstacles. This study recommends strengthening synergy between stakeholders and increasing the institutional capacity of PKBM for the sustainability of non-formal education programs